Breast cancer cells: Focus on the consequences of epithelial-to-mesenchymal transition. (June 2017) - Bong, Alice H.L.; Monteith, Gregory R.
Highlights: Breast tumors are heterogeneous, and cancer cells within a tumor may exhibit epithelial and mesenchymal-like characteristics. Epithelial breast cancer cells can be induced to form mesenchymal-like cells during EMT. The mesenchymal phenotype as a consequence of EMT can be associated with increased resistance to current breast cancer therapies. Abstract: Breast cancers are highly heterogeneous and successful treatment of those subtypes with a high frequency of metastases and resistance to clinically available therapies remains a challenge. An understanding of mechanisms which may contribute to this heterogeneity and generation of more resilient cancer cells is therefore essential. Epithelial-to-mesenchymal transition (EMT) is a dynamic two-way process that occurs during embryonic development and wound healing whereby epithelial cells can gain plasticity and switch to a mesenchymal-like phenotype. EMT has received interest from cancer researchers due to its potential role in processes important in cancer progression and metastasis. Recent evidence has revealed a clear association between EMT and resistance to therapeutics. Targeting of EMT and/or the mesenchymal-like phenotype may be a promising avenue for future therapeutic intervention. This review provides a brief summary of the functional consequences of EMT in breast cancer, with a focus on the mesenchymal-like phenotype.